(Table 1) Mineralogy of sediments at DSDP Site 61-462 - Ulrich Nagel; German Müller; Dieter Schumann (PANGAEA, 1981)
Two holes (462, 462A) were drilled at Site 462 in the Nauru Basin, within an area formed at a fast-spreading Pacific-plate boundary 145 to 155 m.y. ago. Forty-eight sediment samples were received and analyzed by X-ray diffraction according to the methods described in Mann and Müller (1980). Carbonate contents were determined by the "Karbonat-Bombe" method of Müller and Gastner (1971). The upper 447 meters of the sedimentary section at Hole 462 consists of mainly turbiditic, calcareous, and radiolarian oozes, cherts, chalks, and limestones, which are in turn underlain by volcanogenic and zeolitic sandstones and siltstones (447-561 m). Three sedimentary units have been distinguished; Unit IV - below 561 meters - is predominantly basalt and dolerite with interlayered sediments.
Supplement to: Nagel, U et al. (1981): Mineralogy of sediments encountered during Leg 61, as determined by x-ray diffraction. In: Larson, RL; Schlanger, SO; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 61, 563-566, https://doi.org/10.2973/dsdp.proc.61.113.1981